2020
DOI: 10.1021/acscatal.9b04471
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of a Key Conformational Transition in the Mechanism of Peroxiredoxin Sulfinylation

Abstract: Peroxiredoxins from the Prx1 subfamily (Prx) are moonlighting peroxidases that operate in peroxide signaling and are regulated by sulfinylation. Prxs offer a major model of protein–thiol oxidative modification. They react with H 2 O 2 to form a sulfenic acid intermediate that either engages into a disulfide bond, committing the enzyme into its peroxidase cycle, or again reacts with peroxide to produce a sulfinic acid that inactivates the enzyme. Sensitivity to sulf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
14
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 41 publications
7
14
0
Order By: Relevance
“…Instead, the rate constants for condensation between CP-SOH and CR-S -, CP-SOand CR-S -, and CP-SOH and CR-SH all are 2.3-to 5.6-fold higher in PSOH•PSOH than in PSOH•PSS dimers. This is consistent with a scenario where the redox state of the second site induces a conformational change that influences the rate of the FF  LU transition (30) or the FF  LU (quasi-) equilibrium (15) preceding and partially limiting the condensation reactions proper.…”
Section: Discussionsupporting
confidence: 89%
“…Instead, the rate constants for condensation between CP-SOH and CR-S -, CP-SOand CR-S -, and CP-SOH and CR-SH all are 2.3-to 5.6-fold higher in PSOH•PSOH than in PSOH•PSS dimers. This is consistent with a scenario where the redox state of the second site induces a conformational change that influences the rate of the FF  LU transition (30) or the FF  LU (quasi-) equilibrium (15) preceding and partially limiting the condensation reactions proper.…”
Section: Discussionsupporting
confidence: 89%
“…1 A ). The intermediate steps in the oxidation pathway have been well studied ( 18 , 28 , 29 ), but the reduction mechanism is less characterized. Reduction by Trx/TrxR or by GSH/Grx initially involves formation of a mixed disulfide intermediate with either the reactive thiol (C32) of Trx or with GSH ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In a follow-up, the structure of a StAhpC C46S mutant was crystallized (PDB: 1N8J), revealing the resistance of bacterial PRDXs to hyperoxidation in comparison with eukaryotic 2-Cys PRDXs (Wood et al, 2003a(Wood et al, , 2003b in eukaryotic PRDXs possibly responsible for their increased sensitivity to oxidation (GGLG and YF motifs) were identified (Wadley et al, 2016;Wood et al, 2003aWood et al, , 2003b. Interestingly, a recent study on the yeast PRDX Tsa1 found the sensitivity to hyperoxidation not to be linked to the resolution step as expected, but to instead depend on the rates of two competing reactions: the structural transitions from the FF to the LU state as well as the oxidation to the sulfenic acid form (Kriznik et al, 2020).…”
Section: Structural Transitions In the Peroxiredoxin Peroxidase Catalmentioning
confidence: 68%
“…Therefore, local unfolding of helix a 2 containing the active site is necessary to expose the Cp (LU state) in order for the resolving cysteine C R from the other subunit of the dimer to react with C P and form a disulfide bond (Figure 1B). Recent studies suggest that the unfolding of the active site is facilitated by C P sulfenylation (C P -SOH) (Kriznik et al, 2020). Resolution leads to the formation of two disulfide bonds linking the two C P residues within one monomer to the C R residues in the adjacent monomer in the dimer (Figure 1B).…”
Section: Structural Transitions In the Peroxiredoxin Peroxidase Catalmentioning
confidence: 99%